NOUN PHRASES (NPs)-MOVEMENT IN SASAK - Lalu Erwan Husnan (Aksara, 2014)
Sasak is spoken language used by Sasak speakers in Lombok, West Nusa Tenggara. This language is included into Bali-Sasak-Samawa subgroup. Most of the linguists and researchers constructed this language using SVO, but they do not explore the possible movement of the Noun Phrases (NPs) as the basis of constructing its structure. So, it is a need to have the possibility of the NPs movement whether the predicates in Sasak require one or two argument. Data used in this writing are taken through documentary method. They are analyzed using case theory proposed by Chomsky. The analysis shows that both raising verbs and raising adjective involve phrases case. They do not allow structural case movement. In addition, both induce raising. However, they are different in selecting source of NP movement; raising verbs finite or non finite clause, and raising adjective finite clause. Passivization also induces NP-movement in Sasak.Moreover, passive verbs in Sasak can be followed by preposition of locative or not depend on the notion of the verbs used. It has the same analogy with unaccusativity verbs. They lack of internal argument and cannot assign accusative case.